Migration Background and Participation in Continuing Education in Germany : an empirical analysis based on data from the German Socio-Economic Panel study (SOEP) - Öztürk, Halit [Verfasser]; Kaufmann, Katrin [Verfasser] (My University, 2009)
"Europe as an 'immigration continent' is going to become an 'integration continent'. Within this context continuing education has acquired an increasing meaning. Based on the German Socio-Economic Panel (SOEP) study data from 2001-04 the authors examine a broad spectrum of possible factors which may influence participation in continuing vocational education. They focus on the heterogeneity of migrants in Germany and analyse their participation in continuing education in contrast to Germans without a migration background. First, some information on the concept and definition of continuing education in Germany is given. Then, the current status of research regarding participation in continuing education in Germany with a focus on migration background is presented. Human capital theory constitutes the theoretical framework for the analysis. The majority of the hypotheses derived from human capital theory are confirmed by the empirical results. Especially formal qualifications, job position and age turned out to be the parameters that showed the most explanatory results. By estimating the influence of migration background on participation in continuing education the results show that migration background does not generally negatively affect the probability of taking part in continuing vocational education." (Autorenreferat, BIBB-Doku)
Keywords: P 1.5 Migranten; S 1.5 Weiterbildung; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; T 3.5 Statistik; Migrant; Weiterbildungsbeteiligung; Humankapitaltheorie; Empirische Untersuchung; Sozioökonomisches Panel; Quantitative Angaben; 2001-2004